2018
DOI: 10.1021/acs.biochem.8b00061
|View full text |Cite
|
Sign up to set email alerts
|

Surface Charge Modulates Protein–Protein Interactions in Physiologically Relevant Environments

Abstract: Protein–protein interactions are fundamental to biology yet are rarely studied under physiologically relevant conditions where the concentration of macromolecules can exceed 300 g/L. These high concentrations cause cosolute–complex contacts that are absent in dilute buffer. Understanding such interactions is important because they organize the cellular interior. We used 19F nuclear magnetic resonance, the dimer-forming A34F variant of the model protein GB1, and the cosolutes bovine serum albumin (BSA) and lyso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 43 publications
0
61
0
Order By: Relevance
“…At pH 7.5, BSA is predicted to have a charge of −19, while both GB1 dimers are predicted to have a charge of −4. The more-than-predicted stabilization can be explained by electrostatic repulsions between BSA and acidic patches on the surface of each dimer (29).…”
Section: Domain-swappedmentioning
confidence: 96%
See 1 more Smart Citation
“…At pH 7.5, BSA is predicted to have a charge of −19, while both GB1 dimers are predicted to have a charge of −4. The more-than-predicted stabilization can be explained by electrostatic repulsions between BSA and acidic patches on the surface of each dimer (29).…”
Section: Domain-swappedmentioning
confidence: 96%
“…The properties of protein surfaces determine the chemical interactions with cosolutes (29)(30)(31)(32)(33). An advantageous aspect of the GB1 system is that the interactions are similar for both dimers because their primary structures, and hence their surfaces, are highly similar ( Fig.…”
mentioning
confidence: 99%
“…The estimated destabilization free energy determined from the dissociation constants amounts to ∆∆G 0 =1.24-1.31 Kcal/mol, for a temperature range of 260-273 K. A range is given owing to the uncertainty of the freezing temperature. In the following paragraphs, we discuss these results in the context of emerging concepts of how crowding and dimer shapes (85,86), as well as surface charges (87)(88)(89)(90), contribute to dimer cellular stabilities. According to excluded volume theory (91,92), protein association is favored under conditions of macromolecular crowding with concomitant increases in complex stabilities (7,85).…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account only excluded volume effects on in-cell dimer stability is, however, insufficient. Computer simulations and experimental work have shown that soft interactions as well as diffusion can modulate proteinprotein interactions (10,87,93). Contributions can also come from interaction with cellular metabolites and other physiological, small-molecule compounds (94).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation